Dampak Bantuan Subsidi Upah Terhadap Kemiskinan di Indonesia Tahun 2023 - Pelodu, I Gede Ariasa; Wahyuni, Ribut Nurul Tri (Seminar Nasional Official Statistics, 2024)
The COVID-19 pandemic has made poverty alleviation programs in Indonesia less effective. Therefore, the government issued an additional policy, namely the Wage Subsidy Assistance (BSU). This study aims to determine the general picture of BSU recipients and analyze the impact of BSU on poverty in Indonesia using the Propensity Score Matching (PSM) method. This method is used because BSU recipient households must meet certain requirements (not random). The observation unit is individuals aged 15 years and over who meet the criteria for BSU recipients. This study uses the 2023 National Socio-Economic Survey data from BPS-Statistics Indonesia. The results of the study show that the majority of BSU recipients are not poor people. However, the chances of individuals who participate in the BSU program being poor are lower than individuals who do not participate in the BSU program. This shows that the BSU program can be one solution to reducing poverty in Indonesia. Recipients of the BSU policy also need to be evaluated so that they are right on target.